Smart Inventory Management System for Two Zero Two Food - Beh Xin Yi, Cindy; SUHAIMI BIN ABD ISHAK (Applied Information Technology And Computer Science, 2024)
Smart Inventory Management System for Fresh Market is a web-based system, and it is developed especially for Two Zero Two Food in their inventory management. This project is proposed to help fresh markets in tracking their stocks easily and only restock when required as food security threats might happened when there is no proper system to manage stocks in fresh market. This project is developed using waterfall model which the phases move like a waterfall. The development tools that were used to develop this system are Visual Studio Code and XAMPP where phpMyAdmin used as the system database tool for MySQL. This project’s output brings an effective inventory management system. According to user acceptance testing, user very satisfied on this system.